What Is a Citizen Innovation Lab and What Is It For? The Case of LABICxlaPaz - Resina, Jorge (Revista del CLAD Reforma y Democracia, 2019)
Citizen Labs have become a frequent strategy of governments to respond to new social demands. Based on the principles of open innovation and collaborative governance, they emerge as hybrid institutions for the co-production of policies. However, we still know little about the features that define them and their scope. This article aims to provide more information about what happens inside these spaces through a specific experience: the fourth edition of the Laboratories of Civic Innovation (LABIC) promoted by the Ibero-American General Secretariat (SEGIB), held in February 2018 in Nariño, Colombia, and oriented towards the construction of policies for peace. First, a theoretical review about the definition and the characteristics of a laboratory is proposed, to later address the LABICxlaPaz case study. The research is based on field work carried out during the thirteen days in which the laboratory took place and reinforces the hypothesis that, due to its experimental and unstructured nature, the greatest potential of these initiatives is to add a social value to innovative technological solutions that otherwise would hardly be achieved, beyond the specific results on limited ocassions and possible to achieve by other means. Finally, some reflections on its strengths and limitations are raised in order to stimulate the debate.